Desenvolvimento de uma ferramenta computacional no Microsoft Excel para automação dos cálculos de análises de tensões em vigas - Santos, André Luigui Bezerra (Universidade Federal Rural do Semi-Árido, 2020)
Tensions and their transformations are two subjects most discussed by the authors of Resistance of Materials. These stresses are just pressures exerted on internal forces, predominantly or bending moment and shear force, as the main stresses of the beams. It is important to state that I am activating these strains as transversal measures, it will be necessary to analyze all the geometric properties of the studied instructions. Thus, due to a large number of steps and subjects for calculating stressful stresses in beams, or main objective of the work of non-Microsoft Excel analytical models, capable of automatically calculating geometric properties, internal stresses, such as Impressive Stress and its transformations. For this reason, algebraic studies are available for the literature or for these tensions, combined with the adequacy of these equations for each case analyzed. I know that, for this work, we studied cases for sections I, T, rectangular and inverted T, alternating between defined and biaporate beams, with punctual or distributed loads. As a way of validating the results obtained by the spreadsheet, analytical analyzes were performed and compared with the results obtained not in Microsoft Excel. From there, it was concluded that a plan that has an efficient calculation of the tensile stresses, allowing assimilation, that allows to change the dimensions of the studied beams and two profiles, will need to repeat extensive calculations.
Keywords: Tensões; Propriedade Geométricas; Microsoft Excel; Tensions; Geometric Properties; Microsoft Excel; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA